DESKRIPSI LAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA PEMERINTAH DAERAH KABUPATEN/KOTA DI KALIMANTAN TIMUR - Muhammad Kadafi, SE., M.SA; Amirudin Amirudin (Politeknik Negeri Samarinda, 2021)
The purpose of this research is to describe the Realization Report of the Regional Government Revenue and Expenditure Budget District/Cities in East Kalimantan. The things described are the tax ratio, retribution ratio, PAD ratio, dependency ratio, and capital expenditure ratio. This study uses data from 2016-2020 in the form of a report on the Realization of the District/Cities Regional Budget (APBD) in East Kalimantan. The analytical tools used are APBD ratios. Successively the increase/decrease in income, expenditure, surplus/deficit, and financing in 2016 was 8.87%; 26.25%; 109.45%; and 73.83%. In 2017, the increase/decrease in income, expenditure, surplus/deficit, and financing were -14.53%, -11.50%, -146.60%, and 24.42%. In 2018 the increase in income, expenditure, surplus/deficit, and financing were 34.94%, 18.06%, 469.25%, and 2.93%. In 2019, the increase in income, expenditure, surplus/deficit, and financing were 16.60%, 21.45%, 181.07%, and 31.33%. Revenue in 2020 decreased by 4.17%, spending increased by 7.60%, deficit -143.47%, and financing decreased by 66.97%. Overall for the ratio of regional taxes, regional levies and PAD in 2016-2020, the highest ratio is owned by the Cities of Balikpapan, Samarinda, while the lowest is Mahakam Hulu District. All districts/cities in East Kalimantan have a high dependence on transfers from the central government as indicated by the regional dependency ratio. Capital expenditures still dominate district/cities expenditures in East Kalimantan. Keyword : APBD Report, APBD Ratio